A study of the effect of customer citizenship behaviour on service quality, purchase intentions and customer satisfaction. (25th November 2020) - Fotiadis, Thomas
Customer citizenship behaviour constitutes a determinative factor of consumer behaviour. It shapes beliefs relating to the service quality offered by the enterprise and graduates the magnitude of customer satisfaction. This paper investigates customers' behaviour in the light of their intentions to provide information and feedback to the enterprise, to support it in their social circles, to advertise it through 'word-of-mouth', to communicate and interact with other customers and to exchange views, and to detect problems that may emerge due to, for example, delays or shortages in certain products. Additionally, the paper surveys the degree by which the aforementioned constituents affect, the perceived quality of the services rendered, the purchase intention and customer satisfaction. The implicative statistical analysis technique was used to analyse the data of the survey. Results show that feedback and interaction provided by customers shape purchase intention and that these parameters together determine the perceived service quality.